A Study on Petri Net Supporting Tools for System Modeling and Analysis - Damián Varga; Slavomír Šimoňák (Journal of Information and Organizational Sciences, 2023)
Within this work we analyze and compare ten Petri net supporting tools for system modeling and analysis. A short summary of several available overviews of Petri net tools is performed before the tools analysis itself to evaluate the current state in this field. Principal parts of the paper are focused on analysis and evaluation of the selected tools. We provide detailed and practical description of selection of up to date tools, their evaluation based on various criteria, and recommendations for several use cases.